TRANSFORMASI DAN PEMBERDAYAAN UMAT BERBASIS MASJID: Studi Pada Masjid Nurussa’adah Salatiga - M Zulfa M Zulfa (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2015)
This study aimed to answers about the functionality of Nurus Sa’adah Mosque inthe process of transformation and empowerment of community, both on the activities of “mahdhah” and social activities. This study was designed with qualitative descriptive approach. Data analysis was presented by describing the data that has been selected at reductive and draw a phenomenon that occurs on understanding theories that exist both on the theory of the sociology of religion, as well as theories related to social dynamics and social motivation. The results showed that the mosque Nurus Sa’adah, has been able to realize its function as an agent of transformation and empowerment for his congregation. Empowerment is actualized in mahdhah and social activities